Diseño organizacional para el almacén de electrodomésticos “Créditos Miguelito Jr.” de la parroquia San Carlos del cantón Quevedo, a partir del 2012 - Moncada Castro, Diana Carolina (2013)
This research mainly aims to develop an organizational design for the warehouse appliances' CREDIT MIGUELITO JR. ", The same that is intended to facilitate the management an important and necessary for the normal development of the activities of all personnel. To fulfill the objectives were applied methodological tools that allowed to collect important information about each of the activities presently every employee in the store. It was also considered necessary to conduct a situational analysis of stock through the SWOT analysis, which allowed us to establish the strengths, weaknesses, opportunities and threats has in store for this propose alternatives based on exchange and strengthen those that directly affect their progress and growth. With the implementation of the proposal will be achieved by strengthening the goals set by the Organization and in which each member is aware of the extent of its functions and in turn contribute to the organization develops in a more organized environment.